Caracterização vascular periférica de pacientes portadores de glaucoma primário de ângulo aberto - Muller, Elise Vivan Taniguchi [UNIFESP] (2020)
Purpose: To evaluate peripheral microvascular characteristics of primary open-angle glaucoma (POAG) patients and healthy controls, along with endothelin-1 serum concentration and autoantibodies measurements. Patients and Methods: Subjects underwent a visual field test (Humphrey Visual Field Analyzer, Carl Zeiss, Dublin, USA), swept source optical coherence tomography (SS-OCT) (Deep Range Imaging OCT Triton, Topcon, Tokyo, Japan), nailfold capillaroscopy (NFC) (Stereo Microscope SZ40, Olympus, Tokyo, Japan), laser Doppler imaging (LDI) (Moor LDI-VR, Moor Instruments, Axminster, United Kingdom) and venous blood collection. Ophthalmic tests evaluated the presence and the stage of POAG and confirmed the absence of any abnormality among controls. NFC evaluated the presence and the number of microhemorrhages, tortuous capillaries, branched capillaries, dilated capillaries, mega-capillaries and bizarre capillaries, besides the number of capillary loops/mm and the deletion score; LDI measured fingertip blood flow (FBF) in four different timepoints and blood samples were evaluated for determination of serum endothelin-1 concentrations along with serum auto-antibodies measurements. Results: Sixty-eight subjects (43 patients with POAG and 25 healthy controls) were enrolled in the study. 65.1% of POAG patients presented with hemorrhages in the nailfold capillaroscopy versus 25.0% of healthy controls (p=0.003, chi-Square). There was a significant difference in the mean FBF at baseline in POAG patients vs. controls (293.6 ± 100.2 vs. 388.8 ± 52.0 perfusion units [PU]), respectively, p<0.001, mixed models), together with a significant difference in the mean FBF 10 and 20 minutes after cold stimulus in POAG patients in comparison to controls (p<0.001 for all comparisons, mixed models). However, nor the analysis of endothelin-1 concentrations (1.7 ± 1.4 vs. 1.6 ± 1.5 pg/ml, p=0.71, t-test) or the autoantibodies measurements (p>0.05 for all, chi-square) showed any difference between the groups. There was a positive correlation between basal FBF of LDI and retina nerve fiber layer (RNFL) measurements from SS-OCT (r=0.441, p=0.001, Pearson’s correlation coefficient), as well as between basal FBF and the mean deviation index of visual field (r=0.272, p=0.03, Pearson’s correlation coefficient). Conclusions: POAG patients presented significant peripheral microvascular abnormalities compared to healthy controls. This study supports the vascular theory associated to POAG.